2016
DOI: 10.18632/oncotarget.11075
|View full text |Cite
|
Sign up to set email alerts
|

The pseudogene derived long noncoding RNA DUXAP8 promotes gastric cancer cell proliferation and migration via epigenetically silencing PLEKHO1 expression

Abstract: Gastric cancer (GC) is the third leading cause of cancer death due to its poor prognosis and limited treatment options. Evidence indicates that pseudogene-derived long noncoding RNAs (lncRNAs) may be important players in human cancer progression, including GC. In this paper, we report that a newly discovered pseudogene-derived lncRNA named DUXAP8, a 2107-bp RNA, was remarkably upregulated in GC. Additionally, a higher level of DUXAP8 expression in GC was significantly associated with greater tumor size, advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 41 publications
(40 reference statements)
2
91
0
Order By: Relevance
“…Interestingly, these processes are closely related to cancer cells proliferation and invasion. As well as our findings, Sun et al24 reported that DUXAP8 promotes cell proliferation and invasion through repressing EGR1 and RHOB expression in human non small cell lung cancer; Ma et al25 found that DUXAP8 promotes cell proliferation through epigenetically silencing PLEKHO1 expression in gastric cancer. In addition, Kong and colleagues27 revealed that LINC00460 facilitates tumorigenesis by sponging miR‐149‐5p to up‐regulate IL6 in nasopharyngeal carcinoma; Liang et al28 reported that LINC00460 expression is upregulated in ESCC tissues and positively correlated with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, these processes are closely related to cancer cells proliferation and invasion. As well as our findings, Sun et al24 reported that DUXAP8 promotes cell proliferation and invasion through repressing EGR1 and RHOB expression in human non small cell lung cancer; Ma et al25 found that DUXAP8 promotes cell proliferation through epigenetically silencing PLEKHO1 expression in gastric cancer. In addition, Kong and colleagues27 revealed that LINC00460 facilitates tumorigenesis by sponging miR‐149‐5p to up‐regulate IL6 in nasopharyngeal carcinoma; Liang et al28 reported that LINC00460 expression is upregulated in ESCC tissues and positively correlated with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…Among these increased lncRNAs, we found that DUXAP8 and LINC00460 are consistently upregulated in TCGA data and three GEO datasets (Figure 4A,B). Interestingly, DUXAP8 has also been reported to be overexpressed in human non small cell lung cancer,24 gastric cancer25 and renal cell carcinoma,26 while LINC00460 expression is upregulated in nasopharyngeal carcinoma27 and promotes carcinogenesis in ESCC 28. Therefore, we chose these two lncRNAs for further analyses and validation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that expression alterations of lncRNAs are among the driving forces of tumorigenesis. Our previous study identified a pseudogene-derived lncRNA, DUXAP8, that promotes cell proliferation and migration by associating with PRC2 to epigenetically silence PLEKHO1 expression in gastric cancer (GC) [20]. Moreover, lncRNA HOXA-AS2 promotes GC cell proliferation via epigenetically inhibiting P21/PLK3/DDIT3 [21].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the role of lncRNA double homeobox A pseudogene 8 (DUXAP8) has been gradually studied in cancers. Studies show that DUXAP8 exerts a regulatory role in esophageal squamous cell carcinoma, renal cell carcinoma, gastric cancer, and other tumors . A recent study reports that in HCC, DUXAP8 repressed tumor suppressor KLF2 transcription through interacting with EZH2 .…”
Section: Introductionmentioning
confidence: 99%